Competition Policy and Regulation in Power and Telecommunications - Epictetus Patalinghug; Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2005)
Following the global trend in using private sector participation in infrastructure financing and development, the Philippines has largely utilized privatization as a major approach to the development of infrastructure, particularly in power, water, transport, and telecommunications sectors. To provide a legal framework for private sector participation in infrastructure projects, Congress passed the build-operate-transfer (BOT)law, as amended, to expand the scope of private sector involvement in infrastructure provision. Regulatory reform has accompanied the effort to ensure operational efficiency and competitive provision. This paper intends to review and evaluate the regulatory framework that has been established or suggested for the Philippines, focusing on the power and telecommunications sectors. This study will primarily evaluate the existing regulatory framework. It aims to identify issues and gaps, paying particular attention on the competition-related provisions as well as the institutional capacities of regulatory institutions.
Keywords: 330; telecommunications; competition policy; BOT scheme; private sector participation; infrastructure development; regulatory framework; power sector; Electric Power Industry Reform Act (EPIRA); voice over internet protocol (VOIP); Elektrizitätswirtschaft; Telekommunikation; Infrastrukturpolitik; Privatisierung; Wettbewerbspolitik; Regulierung